2021
DOI: 10.1016/j.isci.2021.103271
|View full text |Cite
|
Sign up to set email alerts
|

miR-1307 promotes hepatocarcinogenesis by CALR-OSTC-endoplasmic reticulum protein folding pathway

Abstract: Summary miR-1307 is highly expressed in liver cancer and inhibits methyltransferase protein8. Thereby, miR-1307 inhibits the expression of KDM3A and KDM3B and increases the methylation modification of histone H3 lysine 9, which enhances the expression of endoplasmic-reticulum-related gene CALR. Of note, miR-1307 weakens the binding ability of OSTC to CDK2, CDK4, CyclinD1, and cyclinE and enhances the binding ability of CALR to CDK2, CDK4, CyclinD1, and cyclinE, decreasing of p21WAF1/CIP1, GADD45, pR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…These hub genes displayed especially high expression in 3i/LAF‐PSCs, including HESX1 , important for self‐renewal and pluripotency maintenance, 28,29 as well as SOD2 , ESD , OSTC , NSA2 and PPM1K , which reduce oxidative stress, regulate cell cycle and promote cell survival, respectively (Figure S5D). 30–34 These results reflected the distinctive properties of 3i/LAF‐iPSCs in comparison to other PSCs. To summarize, 3i/LAF‐iPSCs exhibited striking similarities with pgEpiSCs.…”
Section: Resultsmentioning
confidence: 74%
“…These hub genes displayed especially high expression in 3i/LAF‐PSCs, including HESX1 , important for self‐renewal and pluripotency maintenance, 28,29 as well as SOD2 , ESD , OSTC , NSA2 and PPM1K , which reduce oxidative stress, regulate cell cycle and promote cell survival, respectively (Figure S5D). 30–34 These results reflected the distinctive properties of 3i/LAF‐iPSCs in comparison to other PSCs. To summarize, 3i/LAF‐iPSCs exhibited striking similarities with pgEpiSCs.…”
Section: Resultsmentioning
confidence: 74%
“…There is a close relationship between ER stress and oxidative stress in the pathogenesis of pre-eclampsia [72]: two types of intracellular stress are caused by ischaemia-reperfusion and hypoxia, and an unfolded protein response (UPR) in the case of the accumulation of misfolded proteins can activate some of the same intracellular inflammatory signaling pathways as oxidative stress (NF-κB and p38MAPK pathways). In the present study, we identified miR-1307-3p as being an early predictive marker of pre-eclampsia, having the potential to target methyltransferase protein 8 (METTL8), which in turn inhibits the expression of KDM3A/3B and reduces methylation on the ninth lysine of histone H3, therefore providing the binding ability of P300 and RNA pol II to the promoter region of endoplasmic reticulum effector protein CALR [76]. We found a decrease in the miR-1307-3p level in the first-trimester blood serum level of women with early or late PE (Table S4), which indicates the impaired functioning of the endoplasmic reticulum UPR-signaling even before the onset of clinical manifestations of PE.…”
Section: Discussionmentioning
confidence: 93%
“…miR-1307, a gene on human chromosome 10 ( 62 ), can regulate ovarian cancer resistance to chemotherapy and increase the proliferation of prostate cancer cells ( 63 , 64 ). miR-1307 suppresses HCC cell autophagy and accelerates the malignant progression of HCC through the Calr-OSTC endoplasmic reticulum protein folding pathway ( 65 ).…”
Section: Mirnas Involved In the Regulation Of Autophagy In Hccmentioning
confidence: 99%